High frequency of HPV high-risk preventable genotypes in Ecuadorian women with invasive cervical cancer - Gustavo David García Muentes; Fadi Abdul Latif; Claudia Catalina Beltrán Rodríguez; Sebastián Medina González; Juan Carlos Ruiz Cabezas (Revista Panamericana de Salud Pública)
Objective. To determine the distribution of human papillomavirus (HPV) genotypes in invasive cervical cancer samples from Ecuadorian women who attended the Cancer Institute (Sociedad de Lucha Contra el Cáncer – SOLCA). Methods. Archived formalin-fixed paraffin-embedded (FFPE) cervical cancer tissue samples collected during 2017–2021 were deparaffinized, and nucleic acid extraction and purification was performed using silica columns. The obtained nucleic acids were analyzed using INNO-LiPA® HPV Genotyping Extra II per the manufacturer’s specifications. Data were retrieved from records, and HPV genotypes were determined from the FFPE samples. Results. The study included samples from 190 women diagnosed with invasive cervical cancer, with a median age of 52.78 years. Squamous cell carcinoma accounted for 78.94% of the cases, while 21.05% had adenocarcinoma. Among the 190 samples, 80.53% tested positive for HPV DNA, while 19.47% were negative. The most common genotypes detected were HPV 16 (64.05%), 18 (16.99%), and 58 (6.54%). HPV infection frequency was higher in samples from patients with elementary level education (p < 0.05). Conclusions. This study provides valuable insights into the distribution of HPV genotypes in invasive cervical cancer samples from Ecuadorian women. The results indicate an elevated presence of HPV 16, HPV 18, and HPV 58, which are vaccine-preventable genotypes.